2012
DOI: 10.2108/zsj.29.198
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Size Dimorphism and Allometric Growth of Morelet's Crocodiles in Captivity

Abstract: Few studies have conducted morphological analyses of crocodilians, and little information exists on differences between size-classes and sexes in Neotropical crocodilians. In this study, we measured nine morphological traits in 121 captive Morelet's crocodiles Crocodylus moreletii (81 females and 40 males). Our results revealed that individuals < 2 m total length do not exhibit sexual dimorphism in morphometric characteristics. However, for crocodiles over 2 m in length, males were significantly larger than fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 67 publications
(86 reference statements)
0
13
0
Order By: Relevance
“…With BCS, only technical experience is required and, while the validation is subjective, experience is not an important factor in BC categorization (Edmonson et al, 1989). However, the possible effects of sexual dimorphism have been not South American Journal of Herpetology, 16, 2020, 10-15 A Body Condition Score for Crocodilians Ricardo Adrián Ojeda-Adame, Helios Hernández-Hurtado, María Magdalena Ramírez-Martinez, Luis Ignacio Iñiguez-Davalos extensively researched and, therefore, require special attention (Platt et al, 2011;Barrios-Quiroz et al, 2012;Warner et al, 2016), although it has been observed that males have a larger head and body than females in some size classes (Barrios-Quiroz et al, 2012). Despite this, no differences in shape per se have been found between males and females, so we assume that this attribute should not affect the BCS assessment.…”
Section: Discussionmentioning
confidence: 99%
“…With BCS, only technical experience is required and, while the validation is subjective, experience is not an important factor in BC categorization (Edmonson et al, 1989). However, the possible effects of sexual dimorphism have been not South American Journal of Herpetology, 16, 2020, 10-15 A Body Condition Score for Crocodilians Ricardo Adrián Ojeda-Adame, Helios Hernández-Hurtado, María Magdalena Ramírez-Martinez, Luis Ignacio Iñiguez-Davalos extensively researched and, therefore, require special attention (Platt et al, 2011;Barrios-Quiroz et al, 2012;Warner et al, 2016), although it has been observed that males have a larger head and body than females in some size classes (Barrios-Quiroz et al, 2012). Despite this, no differences in shape per se have been found between males and females, so we assume that this attribute should not affect the BCS assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Many crocodile species, including Crocodylus acutus (Cuvier, 1807), Crocodylus moreletii (Duméril and Bibron, 1851), and Crocodylus porosus Schneider, 1801, show sexual size dimorphism when mature, and it is possible to identify males when they exceed the maximum size of females; however, males cannot be distinguished from females of the same size (Platt et al, 2009;Platt et al, 2011;Barrios-Quiroz et al, 2012;Fukuda et al, 2013). Similarly, individuals can be sexed by cloacal palpation or eversion of the penis once they reach a total length greater than approximately 60 cm (Chabreck, 1963;Webb et al, 1984) or 75 cm (Honegger, 1978;Combrink et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Sexual size dimorphism is known in several crocodilian species including American alligators ( Alligator mississippiensis ; Wilkinson & Rhodes, ) and Nile crocodile ( Crocodylus niloticus ; Detoeuf‐Boulade, ; Platt et al, ). However, only a few studies have identified sexual dimorphism in crocodilian head size and shape (e.g., rostrum of gharials ( Gavialis gangeticus ; Hall & Portier, ); skull length and width in Crocodylus moreletti , (Barrios‐Quiroz, Casas‐Andreu, & Escobedo‐Galván, ); interfrontal width of estuarine crocodiles ( C. porosus ; Webb & Messel, ); holistic skull shape of black caiman ( Melanosuchus niger ; Foth, Bona, & Desojo, ), whereas other morphometric studies of skull shape simply were not tested for dimorphism (e.g., Monteiro, Cavalcanti, & Sommer, ) or offered diet‐influenced biomechanical adaptationist hypotheses to explain allometric changes in craniodental features (Blanco, Cassini, & Bona, ) rather than sexual selection. Although Barrios‐Quiroz et al () reported allometric changes in snout shape particularly in the largest size class of captive C. moreletii , no study has sought to correlate pubescent endocrinology and genital development with the potential onset of cranial dimorphism in this or any other species of crocodilian.…”
Section: Introductionmentioning
confidence: 99%